Implementation of Project-Based Learning to Improve Numeracy Skills in Indonesian Primary Schools - Setiti Rahayuningsih; Budiono Budiono; Endang Poerwanti (AL-ISHLAH: Jurnal Pendidikan, 2025)
Indonesia’s education reform through the Minimum Competency Assessment (AKM) emphasizes foundational skills in literacy and numeracy. However, primary schools often struggle to implement numeracy instruction aligned with AKM due to traditional teaching practices. This study investigates how project-based learning (PjBL) can support AKM implementation by enhancing numeracy skills in real-life contexts. This qualitative case study was conducted at SD Muhammadiyah 3 Kota Malang, selected for its innovative pedagogical practices. Data were collected through classroom observations, in-depth interviews with school leaders and teachers, and document analysis of lesson plans and school reports. Thematic analysis was conducted using the Miles and Huberman interactive model, supported by triangulation and member checking to ensure data credibility. The implementation of PjBL in mathematics instruction increased student engagement and improved numeracy competencies, particularly in interpreting data, solving contextual problems, and performing basic calculations. A 15% increase in AKM-related numeracy scores was recorded in the school’s 2023–2024 education quality report. Key themes identified include real-world contextualization, collaborative teacher planning, parental involvement, and student confidence development. PjBL offers a viable approach to integrating AKM in primary education by connecting mathematical concepts with authentic, everyday experiences. This study highlights the importance of whole-school collaboration, contextual instruction, and community engagement in strengthening students’ numeracy outcomes and readiness for competency-based assessments.